Effect of Resting-State fNIRS Scanning Duration on Functional Brain Connectivity and Graph Theory Metrics of Brain Network - Geng, Shujie; Liu, Xiangyu; Biswal, Bharat B.; Niu, Haijing (Frontiers in Neuroscience, 2017)
As an emerging brain imaging technique, functional near infrared spectroscopy (fNIRS) has attracted widespread attention for advancing resting-state functional connectivity (FC) and graph theoretical analyses of brain networks. However, it remains largely unknown how the duration of the fNIRS signal scanning is related to stable and reproducible functional brain network features. To answer this question, we collected resting-state fNIRS signals (10-minute duration, two runs) from 18 participants and then truncated the hemodynamic time series into 30-second time bins that ranged from 1 to 10 minutes. Measures of nodal efficiency, nodal betweenness, network local efficiency, global efficiency and clustering coefficient were computed for each subject at each fNIRS signal acquisition duration. Analyses of the stability and between-run reproducibility were performed to identify optimal time length for each measure. We found that the FC, nodal efficiency and nodal betweenness stabilized and were reproducible after 1 minute of fNIRS signal acquisition, whereas network clustering coefficient, local and global efficiencies stabilized after 1 minute and were reproducible after 5 minutes of fNIRS signal acquisition for only local and global efficiencies. These quantitative results provide direct evidence regarding the choice of the resting-state fNIRS scanning duration for functional brain connectivity and topological metric stability of brain network connectivity.